Early History of Adsorption Measurements - Erich Robens; Shanath Amarasiri A. Jayaweera (Adsorption Science & Technology)
This historical survey covers the initial investigations of adsorption measurements of the geometric microstructure of solid surfaces. Methods investigated are sorptometry, hygrometry, calorimetry, thermogravimetry and thermoporometry. The histories of these methods are short, beginning in modern times; only hygrometry can be traced back to ancient times.